Primary cell cultures for the personalized therapy in aggressive thyroid cancer of follicular origin. (February 2022) - Fallahi, Poupak; Ferrari, Silvia Martina; Elia, Giusy; Ragusa, Francesca; Patrizio, Armando; Paparo, Sabrina Rosaria; Marone, Gianni; Galdiero, Maria Rosaria; Guglielmi, Giovanni; Foddis, Rudy; Cristaudo, Alfonso; Antonelli, Alessandro
Abstract: Thyroid cancer (TC) is the most prevalent endocrine malignancy. More than 90 % of TC is represented by differentiated TC (DTC) arising from the follicular thyroid cells. DTC includes papillary TC (PTC), follicular TC (FTC), and Hürthle cell TC. Anaplastic TC (ATC) accounts for 1% of TC, and it represents 15–40 % of TC death. Current treatment strategies are not completely effective against aggressive DTC or ATC, and mortality is one of the most important challenges. Recently, progresses have been obtained in the understanding of the molecular/genetic basis of TC progression, and new drugs have been introduced [ i.e. tyrosine kinase inhibitors (TKIs)], able to block the oncogenic or signaling kinases, associated with cellular growth. Thyroid cell lines, obtained from tumoral cells and chosen for high proliferation in vitro, have been used as preclinical models. Actually, these cells lose the characteristic features of the primary tumor, because they adapt to in vitro growth conditions. For these reasons, the use of these cell lines has important limitations, and more recently human primary cell cultures have been established as monolayer cultures, and investigated for their biological behavior. Moreover, in the past, primary TC cells could be collected only through surgical biopsies, while recently human primary cell cultures can be established also from samples of fine-needle aspiration citology from aggressive dedifferentiated DTC or ATC. Testing in vitro different TKIs in each patient can help to develop new personalized treatments, without using ineffective drugs. In conclusion, personalized medicine and precise oncology, which consider both patients and their disease features, represent the future of the treatment approach, and further progress is needed in this direction.